2005
DOI: 10.1097/01.ico.0000159734.75672.c4
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary in vitro Evaluation of 2-Octyl Cyanoacrylate (Dermabond??) to Seal Corneal Incisions

Abstract: The mean leakage pressures were comparable for the 2 groups. Either method of closure should be able to withstand any postoperative increases in intraocular pressure. Dermabond adhesive may be considered as an alternative to conventional sutures in corneal wound closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 8 publications
(5 reference statements)
1
17
0
2
Order By: Relevance
“…In this experiment, increase in mucous secretion was also related only to traumatism caused in the cornea during keratectomy, since both the adhesive-treated group and the control group presented similar levels. This response to aggression showed that the lesion present in the cornea also affected the conjunctiva, which indicates the existence of an integrated mechanism of response to diseases that attack structures present at the ocular surface; such fact was also reported for animals subjected to keratoplasty (10,27). The clinical test did not show edema in the periphery of lesions in animals subjected to keratoplasty using fibrin glue, which indicates that the adhesive acted as an impermeable material, avoiding water penetration and consequent stroma hydration.…”
Section: R L Sampaio Et Al Use Of Fibrin Glue Derived From Snake Vmentioning
confidence: 95%
See 1 more Smart Citation
“…In this experiment, increase in mucous secretion was also related only to traumatism caused in the cornea during keratectomy, since both the adhesive-treated group and the control group presented similar levels. This response to aggression showed that the lesion present in the cornea also affected the conjunctiva, which indicates the existence of an integrated mechanism of response to diseases that attack structures present at the ocular surface; such fact was also reported for animals subjected to keratoplasty (10,27). The clinical test did not show edema in the periphery of lesions in animals subjected to keratoplasty using fibrin glue, which indicates that the adhesive acted as an impermeable material, avoiding water penetration and consequent stroma hydration.…”
Section: R L Sampaio Et Al Use Of Fibrin Glue Derived From Snake Vmentioning
confidence: 95%
“…Thus, several substances, such as mixture of casein and polyvinyl alcohol, derived from rubber, polyacrylate, epoxy resin, formaldehyde resin and cyanoacrylate adhesive, were tested; however, they showed to have irritating action on ocular tissues with no effective contribution to healing (6,9,12,26,27,31). familiaris, LINNAEUS, 1758).…”
Section: Introductionmentioning
confidence: 99%
“…2-Octyl cyanoacrylate, or Dermabond™ (Ethicon, West Somerville, NJ, USA) is a new adhesive intended for topical application to hold closed easily approximated skin edges of wounds from surgical incisions [1][2][3].…”
Section: To the Editormentioning
confidence: 99%
“…Certaines voies d'abord en chirurgie orbitaire ou esthétique se font de plus en plus par la conjonctive afi n de laisser un minimum de cicatrices (sutures au Vicryl® 8/0 ou pas, selon les indications). Enfi n, citons la possibilité récente de suturer des incisions cornéennes avec une colle acrylique (14).…”
Section: Microchirurgie Ophtalmologiqueunclassified